An umbrella review on treatments and therapeutic options for COVID-19 - SeyedAhmad SeyedAlinaghi; Amir M. Afsahi; Ayoob Molla; Pegah Mirzapour; Ramin Shahidi; Haleh Siami; Farid F. Rad; Faeze Abbaspour; Navid Mozafari; Kamal Fakhredini; Esmaeil Mehraeen; Omid Dadras (Инфекция и иммунитет, 2023)
Introduction. As the COVID-19 pandemic continues to pose a significant challenge to global health, effective therapeutic options for preventing and treating the disease have become increasingly important. We aimed to provide an update on current treatments and therapeutic options for COVID-19 patients.Materials and methods. The purpose of this umbrella review is to explore the current treatments and therapeutic options for COVID-19 patients. Keywords and their combinations were searched across online databases in Embase, PubMed/MEDLINE, Web of Science, and Scopus spanning from July 1, 2020, through March 3, 2023. Publications were selected for data extraction in two steps based on the study inclusion/exclusion criteria. The study adheres to the PRISMA checklist as well as NIH bias risk and quality assessment tool.Results. In this review, 28 relevant articles were selected for the final qualitative synthesis. The majority of included studies had reported on the efficacy of Lopinavir/Ritonavir (n = 4), Ivermectin (n = 3), Baricitinib (n = 2), Tocilizumab (n = 2), Remdesivir (n = 2), ACEI/ARB (n = 2), Vitamin D (n = 2), Molnupiravir (n = 2), Traditional Chinese medicine (TCM) (n = 2), Convalescent plasma transfusion (CPT) (n = 2) and hydroxychloroquine (n = 2) in treating COVID-19. It appeared that Baricitinib, Remdesivir, ACEI/ARB, TCM, and CPT may have beneficial effects on reducing mortality, hospitalization duration, and disease severity in COVID-19 patients. Other interventions, such as Lopinavir/Ritonavir, Ivermectin, Vitamin D, and Hydroxychloroquine did not show clear benefits or had inconclusive results.Conclusion. This umbrella review provides a comprehensive overview of the current evidence on the effectiveness and safety of various pharmacological and non-pharmacological interventions for COVID-19. These results provide an updated overview of the current landscape for COVID-19 treatments, highlighting potential avenues for further research and clinical practice. It is crucial to continue monitoring emerging evidence and conducting rigorous studies to guide the development and optimization of therapeutic strategies against COVID-19.